PEMBERIAN ASI EKSKLUSIF DAN PROBLEMATIKA IBU MENYUSUI - Mustofa, Ahmad (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2010)
Breast milk, especially if it is given exclusively is the best first food for babies after birth. Babies will get a sufficient intake ofnutrients and essential substances such as immune substances so that he can grow normally both physically and psychologically. For themother who gives breast to her baby will get positive benefits for the health of post-childbirth. Some issues become an obstacle in the field sothat not all babies get the best food. Message of the Qur’an is therefore important to note that in addition to containing directives life, thereare practical solutions to problems such as breast-feeding mothers who can not breast-feeding her child with the mother dairy.